Strategi Peningkatan Engagement Melalui Penguatan Perceived Organization Support dan Servant Leadership (Studi Komparatif Menggunakan Analisis Regresi Pada Perawat Rumah Sakit Pemerintah dan Rumah Sakit Swasta di Kota Semarang) - Soeyono, Annisaa; Notosudjono, Didik; Sunaryo, Widodo (Jurnal Locus Penelitian dan Pengabdian, 2026)
According to data collected by the Ministry of Health, negative growth in the number of nurses at regional hospitals (-3.9%) and at RSS (-10.3%) occurred in 2022-2023. This indicates a problem with nurse engagement. The purpose of this study was to find strategies to improve nurse engagement in government and private hospitals. The population of nurses at government hospitals was 158 respondents. The population of nurses at private hospitals was 154 respondents. This study used survey methods, comparative analysis, regression analysis, and qualitative analysis. The results of the study found that there is a significant positive direct effect of Perceived Organization Support on the engagement of nurses in government hospitals, there is a significant positive direct effect of Servant Leadership on the engagement of nurses in government hospitals, there is a positive influence of perceived organization support and servant leadership, simultaneously on the engagement of nurses in government hospitals, there is a significant positive direct effect of Perceived Organization Support on the engagement of nurses in private hospitals, there is a significant positive direct effect of Servant Leadership on the engagement of nurses in private hospitals, there is an insignificant difference in the influence of engagement on perceived organization support between nurses in government hospitals and private hospitals, there is an insignificant difference in the influence of engagement on servant leadership between nurses in government hospitals and private hospitals.